KEBERMAKNAAN HIDUP PADA WANITA YANG BELUM MEMILIKI ANAK TANPA DISENGAJA (INVOLUNTARY CHILDLESS) - IRIANI INDRI HAPSARI; SITI RIANISA SEPTIANI (Journal of Research and Measurement in Psychology, 2015)
Generally, married women are willing to have a child, but not all women are having opportunity to be a mother. Veevers (Miall, 1986) defined involuntary childless as psychological desire to have children yet unable to have them. This research aimed to identify the meaning of life of involuntary childless women. This research used qualitative method approach with Interpretative Phenomenological Analysis (IPA). Subject of this research was three involuntary childless womens. Data collection techniques used were interview with guidelines. The conclussion of the three cases from this study is the subjects have differences in the process of searching for meaning of life. In these cases has emerged themes on the four stages of the search for meaning of life.